2021
DOI: 10.1186/s13063-021-05428-w
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast for genital erosive lichen planus in women (the AP-GELP Study): study protocol for a randomised placebo-controlled clinical trial

Abstract: Background Genital erosive lichen planus (GELP) is a genital subtype of lichen planus, a chronic autoimmune inflammatory disease of unknown aetiology. In women, GELP is characterised by painful vulvo-vaginal mucosal erosions and scarring, often resulting in poor sexual health and reduced quality of life. Treatment options are limited and often with little effect. Apremilast, a phosphodiesterase 4-inhibitor, has been shown to have a positive effect on psoriasis and other inflammatory skin diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Subsequently, a total of 5 LP patients, mostly with treatment-refractory disease, were reported to improve when treated with apremilast (203)(204)(205). Based on these reports, apremilast is currently evaluated in a randomized placebo-controlled clinical trial in women with genital erosive lichen planus (206). Currently, patients are recruited to this study (NCT03656666).…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…Subsequently, a total of 5 LP patients, mostly with treatment-refractory disease, were reported to improve when treated with apremilast (203)(204)(205). Based on these reports, apremilast is currently evaluated in a randomized placebo-controlled clinical trial in women with genital erosive lichen planus (206). Currently, patients are recruited to this study (NCT03656666).…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…Nevertheless, we are optimistic that these challenges can be overcome in our RCT, which we are conducting in a dermato-gynaecology centre with a large patient base and a high referral rate. Most recently, Skullerud et al published the study protocol of their double-blinded RCT [ 20 ]. However, their study compared apremilast with placebo and not other systemic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The trial is a randomized, placebo-controlled clinical trial based in Norway, lasting 24 weeks. A single open-label study in 2013 with 10 patients showed this treatment to be efficacious [17 ▪ ]. While it is difficult to perform large randomized, placebo-controlled trials on more rare disease states, hopefully, more studies will investigate more effective treatments for lichen planus.…”
Section: Lichen Planusmentioning
confidence: 99%
“…The gold-standard treatment for lichen planus is topical high-potency corticosteroids like clobetasol propionate 0.05%. Second-line treatment options include calcineurin inhibitors like tacrolimus or even systemic immunosuppressants such as prednisolone, retinoids, methotrexate, cyclophosphamide, azathioprine, and mycophenolate mofetil [17 ▪ ]. Data for systemic treatment and robust clinical trials are indeed lacking and often only include small groups or case series [18].…”
Section: Lichen Planusmentioning
confidence: 99%